Analisis Dampak Kebijakan Pemberhentian Tidak Dengan Hormat Pegawai Negeri Sipil Karena Melakukan Tindak Pidana Kejahatan Jabatan Atau Tindak Pidana Kejahatan Yang Ada Hubungannya Dengan Jabatan - Mulyono, Adi (Faculty of Law, Universitas Muhammadiyah Pontianak, 2022)
Dismissal is not done with respect to a Civil Servant, because he was sentenced to imprisonment or confinement after receiving a court decision that incraht on a crime of office crime or criminal offenses related to his position. This public policy is implemented based on the Law on State Civil Apparatus and the Government Regulation on the Management of Civil Servants.This article describes the public policies set by the government for civil servants who have been convicted by the Corruption Court and whose decisions have permanent legal status as the basis for implementing dishonorable dismissals, positive impact of policies, legal and social impacts on civil servants convicted of corruption, and policy comparisons to politicians. convicted of corruption.It was concluded that this good step in realizing a clean government free from KKN, apart from having a positive impact, could actually have a negative impact on civil servants. The negative impact is in the form of potential neglect of human rights that occurs because all cases end with PTDH regardless of the level of error, even because of administrative errors in carrying out their duties, career as a civil servant will be over.The solution that can be done is to review and harmonize Government Regulations on the Management of Civil Servants and their derivative regulations. In the new regulatory system, all corruption criminal decisions are examined in ASN courts/trials which will result in orders for final punishment to civil service supervisors to punish PNS convicted of corruption according to the level of error as stated in the Government Regulation concerning Civil Servant Discipline.